Frontispiece: Deciphering the Crystal Structure of a Scarce 1D Polymeric Thorium Peroxo Sulfate. Issue 41 (22nd July 2019) - Bonato, Laura; Virot, Matthieu; Dumas, Thomas; Mesbah, Adel; Lecante, Pierre; Prieur, Damien; Le Goff, Xavier; Hennig, Christoph; Dacheux, Nicolas; Moisy, Philippe; Nikitenko, Sergey I.
Abstract : Tetravalent actinide peroxides and related structures have been very poorly reported in the literature. A combination of synchrotron XRD and EXAFS techniques allowed to solve the structure of an original Th peroxo sulfate dihydrate, Th(O2 )(SO4 )(H2 O)2, which crystallizes in the Pna 21 space group of the orthorhombic system in the form of polymeric microfibres. Peroxide ligands coordinate to Th cations with a rare μ3 –η 2 :η 2 :η 2 bridging mode, forming infinite 1D chains decorated simultaneously with monodentate and bidentate sulfato ligands. For more details, see the Communication from M. Virot et al. onpage 9580 ff.